Role of Yoga in Improving Mental Health of Citizens of India During the Out-Break of Covid -19 Pandemic: Addressing Mental Health Challenges during the COVID-19 Pandemic with Yoga (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The outbreak of Corona Virus Disease 19 (COVID-19) pandemic is exceptional and unique innumerous ways. It has raised a question mark on the health care system of the country with a death tollof 12237, 160384 active cases and 194324 cured and discharged till date. At this moment, every one ofus is forced to stay indoors and work distantly around the clock in order to maintain the socialdistancing so as to protect us from this pandemic. This physical barrier is known as a lockdown. All thishas resulted in reducing our social activities which have created a feeling of trapped or loneliness sincewe are detached from our loved ones. This lockdown has made us sad, depressed, disheartened,worried, stressed, nervous and fearful affecting and destroying our mental health so badly that it haseven reported the cases of suicide. Mental health is a vital facet of an individual. It has a tremendousimpact on our personal and professional life. Hence, requires immense attention during this lockdownperiod so as to fight against this Corona Virus. There is a direct relationship between our body andmind. We can stay safe and healthy during this pandemic only if manage to keep ourselves mentally fitand strong.Yoga is a vital instrument which can help individuals to boost immunity and improve their respiratoryhealth. Yoga and meditation together have a potential to build an extra positive health. Both can help inpreventing and healing from COVID-19. Even the Government of India through its Ministry of AYUSH,has too stressed on yoga and meditation and issued a very practical and functional recommendationsin this perspective. Yoga provides us empowerment and authorizes us to take charge of our own life,consequently encouraging holistic health for every human being on this planet. This paper discussesthe growing concern of anxiety, fear and nervousness caused due to corona virus in deteriorating themental health of citizens of the country and thus, highlighting the role of yoga and meditation in thisdirection to boost immunity and respiratory health to fight against this pandemic.